Molecular mechanisms regulating reproduction in the presence and absence of the hypophysiotropic GnRH in zebrafish females - Tanaka, Sakura (My University, 2022)
Gonadotropin-releasing hormone (GnRH) is an essential neuropeptide for inducing the luteinizing hormone (LH) secretion in vertebrates. Most vertebrates possess two or three GnRH isoforms, and GnRH1 is known as a regulator of reproduction, especially the LH secretion. The zebrafish lost GnRH1 during evolution, and another GnRH, GnRH3, is considered to function similarly to GnRH1 in regulating the LH secretion. However, previous studies exhibited that the GnRH3 knockout does not affect fertility in zebrafish. This finding may be explained by functional compensation or redundancy that mitigates the absence of GnRH3. The present study depicts evidence supporting the functional redundancy theory and pointing to GnRH3 dispensability in modulating the LH secretion in zebrafish. To determine the role of the GnRH3 and its neurons in controlling ovulation in zebrafish, conditional GnRH3 neuronal ablation in adult fish was performed, which, however, resulted in no effects on fertility. Next, to examine whether other neuropeptides can regulate LH secretion, this study demonstrated that another neuropeptide, vasoactive intestinal peptide (Vip), induces LH secretion in zebrafish. Intracerebroventricular administration of Vip augmented plasma LH levels in wild-type (WT) and gnrh3/ females, with no changes in pituitary GnRH3 content. These findings indicate that Vip induces LH release, by acting with or through a non-GnRH3 factor(s). Finally, to determine whether the absence of GnRH3 affects pituitary states, and to identify potential factors pertinent to the LH secretion, expression profiles of individual pituitary cells of WT and gnrh3/ female zebrafish were analyzed by single-cell transcriptomics. In LH gonadotropes, there were no differences in LH secretion-related gene expressions between the genotypes, but some non-reproductive hormone gene expression was increased in gnrh3/. A potential novel cell type was also classified in WT, which was barely detectable in gnrh3/. These changes suggest that GnRH3 suppresses the expression of certain genes that contribute to the pituitary cell specialization. Taken altogether, GnRH3 may not work solely as critical factors in inducing the LH secretion in zebrafish, which is likely stimulated through functional redundancy. The present study provides novel evidence that supports the concept of a GnRH-independent system in vertebrate reproduction.
Keywords: fertility; GnRH; LH; ovulation; reproduction; zebrafish